The Influence of Emergency Programs on Self Efficacy and Helping Motivation of Adolescents in Tourism Villages - Suindrayasa, I Made; Manangkot, Meril Valentine (Journal of A Sustainable Global South; Vol 7 No 1 (2023): February 2023DO - 10.24843/jsgs.2023.v07.i01.p05, 2023)
Bali tourism industry must be supported by various aspects, especially health aspect. Tourist villages in Bali are developing. Emergency conditions such as traffic accidents and disasters are situations that can happen anywhere, to anyone, and at any time. Good preparation, prevention, and handling of emergency conditions will provide a sense of security for visiting tourists and tourism service actors in tourist villages. Tourism villages have never provided information about preparation, prevention, and handling when an emergency occurs. When emergency situation occurs, the community only waits or immediately takes the victim to health services. Teenagers are expected to be bystanders in their environment. This study aims to determine the effect of an emergency program on increasing self-confidence (self-efficacy) and motivation to help someone in an emergency. An emergency program is a program that consists of material and emergency concepts that can be applied to community settings. This study used a quantitative method using a pre-experimental research design. The sample in this study were people in tourist villages who were willing to become respondents, namely 85. The results of this study showed that there was an influence of emergency programs on self-efficacy (p-value = 0,007) and motivation to help (p-value = 0,001) in adolescents in tourist villages. From the results of this study, it is hoped that the emergency program will become one of the intervention recommendations in an effort to increase self-efficacy and motivation to help people in emergency situations.